Estudio de la cantidad de gas metano emanado al ambiente producto de la descomposición de los desechos sólidos en la celda emergente de la Mancomunidad Pujilí/Saquisilí, en el sector Inchapo del cantón Pujilí - León Semblante (2019)
This research was to identify the possible atmospheric contamination generated by the emergent cell of the Pujilí - Saquisilí Commonwealth, to determine the concentration and emanation of methane gas produced by the decomposition of solid waste. The processes of decomposition of waste favor the emission of products contaminants that can be a potential risk to the environment and health, making measurements of methane with the PCE-7755 equipment, with the regulations of the EU (European Union) by Directive 92/42 / CEE through Royal Decree 275/1995, and the TESTO-350 combustion gas analyzer box, which evaluated the O2, CO2 gases, according to the international regulations (USEPA) of the United States Environmental Protection Agency, where the monitoring and evaluation protocols established in TULSMA are governed, Book VI, Annex 3. This investigation was conducted for ten months and was divided into two parts to meet the objectives raised, in the first part a diagnosis of the area of studies was made, which included interviews with administrators and workers to know the current environmental problems that was evidenced in the monitors in the second part, with the information collected in the field was obtained the following results, as the main methane gas CH4 with the emanation of three combustion chimneys, with a minimum of 0.4ppm and a maximum of 0.7ppm, obtaining an average of 0.61ppm emanation, which are within the permissible limits according to the measurement of PCE-7755 equipment with EU regulations that have a minimum of 0.5ppm and maximum 1ppm with regulations in force since February 24, 1995. The management of the commonwealth and its workers will take into account the emission analysis with the objective of improving the environmental quality of the air of the Pujilí Canton.